PEMILIHAN PROTOKOL VIRTUAL PRIVATE NETWORK MENGGUNAKAN MIKROTIK UNTUK KEBUTUHAN AKSES JARAK JAUH PADA SMK NEGERI 11 MALANG - Ramadhanti, Rizka Laela Saputri; Zaini, Ahkmad; Nugraha, Danang Aditya (Jurnal Fakultas Teknologi Informasi, 2025)
State Vocational School 11 Malang is a school that uses technology and information. Administrators have the duty to monitor and understand the condition of the school network. The problem when the administrator is outside the local network or public network. The administrator needs remote access to access the server or application safely without data leakage. VPN provides security by encrypting internet traffic. PPTP, L2TP, OpenVPN are VPN protocol options that can be used to connect between different networks. In this research, testing was carried out between these protocols to find out which one has the best performance and the ability to maintain the confidentiality of the data and information stored in it.